Characteristics and mechanisms of catalytic ozonation with Fe-shaving-based catalyst in industrial wastewater advanced treatment. (10th June 2019) - Li, Xufang; Chen, Weiyu; Ma, Luming; Huang, Yuanxing; Wang, Hongwu
Abstract: Iron shavings were modified and used as the catalyst (named as Fe-shaving-based catalyst) for the ozonation of bio-treated coking wastewater. The difference of organic pollutants oxidation between catalytic and sole ozonation processes was characterized by MW (Molecular Weight) distribution and 3DEEM (Three-dimensional Excitation and Emission Matrix Fluorescence) analysis. Removals of the pollutants with MW of 5–10 kDa and 10–20 kDa in catalytic ozonation process were 81.5% and 85.2%, which were far better than that in sole ozonation process (31.1% and 41.8%). Organics with MW of 0.3–2 kDa and 2–5 kDa would accumulate in both two processes, while the accumulation amount in catalytic ozonation process was half of it in sole ozonation process. The removal of fluorescent substances in catalytic ozonation process experienced a procedure of lower firstly (<15 min) and then higher (>15 min) than that in sole ozonation process. The slight residual fluorescent substances were completely removed in catalytic ozonation process, while remained unchanged in sole ozonation process with the reaction time increasing to 180 min. The catalytic effect of Fe-shaving-based catalyst was better than commonly used powder catalysts and the TOC (Total Organic Carbon) removal attained to 78%. Hydroxyl radicals (·OH) were confirmed to be the effective oxidant in catalytic ozonation process through inhibition experiments. The cumulative ·OH formations with 200 g/L Fe-shaving-based catalyst during 180 min were 362 μmol, which explained the better catalytic effect of it. The surface hydroxyl groups were determined to be the most probable active sites for ·OH generation through phosphate inhibition experiments. Besides the excellent catalytic effect, using Fe-shaving-based catalyst provided a feasible resource utilization method of industrial waste Fe-shavings. Thereby, it is a promising catalyst for practical industrial wastewater advanced treatment with catalytic ozonation process. Highlights: Organics oxidation order of catalytic ozonation was compared with sole ozonation. Fe-shaving-based catalyst played significant catalytic effect to ozonation. Catalytic ozonation process could remove fluorescent substances thoroughly. Surface hydroxyl groups were the dominating active catalytic sites. The cumulative ·OH formation was first measured to be 361 μmol.